Strategic planning and educational marketing: An analysis of a technical school in São Paulo (Research, Society and Development, 2026)
This study analyzed, over eighteen months, the educational marketing practices developed by a technical school linked to the Centro Paula Souza, located in the interior of the state of São Paulo. The research, characterized as action research, articulated theoretical foundation and practical intervention, involving bibliographic research, document analysis, dialogue with managers, and the development of a strategic marketing plan. The central objective was to understand how institutional dissemination actions have been implemented and to propose strategies to increase the school's visibility and the number of candidates for the selection process (Vestibulinho). Elements such as the 4Ps of marketing, digital marketing, institutional lectures, and internal marketing were analyzed, in addition to the application of the 5W2H tool. The results indicate that, although there are relevant initiatives, there is a need for greater systematization and integration of actions. It is concluded that educational marketing can strengthen the institutional image and expand the social impact of the school.